Transcranial Alternating Current Stimulation (tACS) Enhances Mental Rotation Performance during and after Stimulation - Kasten, Florian H.; Herrmann, Christoph S. (Frontiers in Human Neuroscience, 2017)
Transcranial alternating current stimulation (tACS) has been repeatedly demonstrated to modulate endogenous brain oscillations in a frequency specific manner. Thus, it is a promising tool to uncover causal relationships between brain oscillations and behavior or perception. While tACS has been shown to elicit a physiological aftereffect for up to 70 minutes, it remains unclear whether the effect can still be elicited if subjects perform a complex task interacting with the stimulated frequency band. In addition, it has not yet been investigated whether the aftereffect is behaviorally relevant. In the current experiment, participants performed a Shepard-like mental rotation task for 80 minutes. After 10 minutes of baseline measurement, participants received either 20 minutes of tACS at their individual alpha frequency (IAF) or sham stimulation (30 seconds tACS in the beginning of the stimulation period). Afterwards another 50 minutes of post-stimulation EEG were recorded. Task performance and EEG were acquired during the whole experiment. While there were no effects of tACS on reaction times or event-related-potentials, results reveal an increase in mental rotation performance in the stimulation group as compared to sham both during and after stimulation. This was accompanied by increased ongoing alpha power and coherence as well as event-related-desynchronization in the alpha band in the stimulation group. The current study demonstrates a behavioral and physiological aftereffect of tACS in parallel. This indicates that it is possible to elicit aftereffects of tACS during tasks interacting with the alpha band. Therefore, the tACS aftereffect is suitable to achieve an experimental manipulation.